Metabolomics Exploration of Pseudorabies Virus Reprogramming Metabolic Profiles of PK-15 Cells to Enhance Viral Replication - Gou, Hongchao; Bian, Zhibiao; Li, Yan; Cai, Rujian; Jiang, Zhiyong; Song, Shuai; Zhang, Kunli; Chu, Pinpin; Yang, Dongxia; Li, Chunling (Frontiers in Cellular and Infection Microbiology, 2021)
For viral replication to occur in host cells, low-molecular-weight metabolites are necessary for virion assembly. Recently, metabolomics has shown great promise in uncovering the highly complex mechanisms associated with virus-host interactions. In this study, the metabolic networks in PK-15 cells infected with a variant virulent or classical attenuated pseudorabies virus (PRV) strains were explored using gas chromatography-mass spectrometry (GC-MS) analysis. Although total numbers of metabolites whose levels were altered by infection with the variant virulent strain or the classical attenuated strain were different at 8 and 16 hours post infection (hpi), the predicted levels of differential metabolic components were shown to be associated with specific pathways, including glycolysis as well as amino acid and nucleotide metabolism. The glucose depletion and glycolysis inhibitors 2DG and oxamate could reduce the level of PRV replication in PK-15 cells. In addition, the inhibition of the pentose phosphate pathway (PPP) resulted in an obvious decline of viral titers, but the prevention of oxidative phosphorylation in the tricarboxylic acid（TCA）cycle had a minimal effect on viral replication. Glutamine starvation resulted in the decline of viral titers, which could be restored by supplemental addition in the culture media. However, inhibition of glutaminase (GLS) activity or the supplement of 2-ketoglutarate into glutamine-deleted DMEM did not alter PRV replication in PK-15 cells. The results of the current study indicate that PRV reprograms the metabolic activities of PK-15 cells. The metabolic flux from glycolysis, PPP and glutamine metabolism to nucleotide biosynthesis was essential for PRV to enhance its replication. This study will help to identify the biochemical materials utilized by PRV replication in host cells, and this knowledge can aid in developing new antiviral strategies.